On the order of exponential growth of the solution of the linear difference equation with periodic coefficient in Banach space - H. Attia Hussein (International Journal of Mathematics and Mathematical Sciences)
An equation of the form y−A(t)y=f(t) is considered, where Δy=y(t+δ)−y(t)δ, and the necessary and sufficient criteria for the exponential growth of the solution of this equation is obtained.